2020
DOI: 10.1186/s40902-020-00250-x
|View full text |Cite
|
Sign up to set email alerts
|

Why most patients do not exhibit obstructive sleep apnea after mandibular setback surgery?

Abstract: Maxillomandibular advancement (MMA) is effective for the treatment of obstructive sleep apnea (OSA). In previous studies, the airway was increased in the anteroposterior and transverse dimensions after MMA. However, the effect of the opposite of mandibular movement (mandibular setback) on the airway is still controversial. Mandibular setback surgery has been suggested to be one of the risk factors in the development of sleep apnea. Previous studies have found that mandibular setback surgery could reduce the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 63 publications
0
29
0
3
Order By: Relevance
“…Wolford and Cottrell [11] described 18 clinical features of macroglossia to determine whether a tongue reduction is necessary. Eight of these features were observed in this case: (1) a wide, broad, and flat tongue; (2) open bite; (3) mandibular prognathism; (4) Class III malocclusion; (5) chronic posturing of the tongue between the teeth at the rest; (6) buccal tipping of posterior teeth; (7) increased transverse width of dental arch; (8) instability in orthodontic treatment. All these features were observed at the initial evaluation and were still significant following pre-surgical orthodontic treatment.…”
Section: Diagnosis and Etiologymentioning
confidence: 80%
See 1 more Smart Citation
“…Wolford and Cottrell [11] described 18 clinical features of macroglossia to determine whether a tongue reduction is necessary. Eight of these features were observed in this case: (1) a wide, broad, and flat tongue; (2) open bite; (3) mandibular prognathism; (4) Class III malocclusion; (5) chronic posturing of the tongue between the teeth at the rest; (6) buccal tipping of posterior teeth; (7) increased transverse width of dental arch; (8) instability in orthodontic treatment. All these features were observed at the initial evaluation and were still significant following pre-surgical orthodontic treatment.…”
Section: Diagnosis and Etiologymentioning
confidence: 80%
“…Article in Press the mandibular setback and development of sleep apnea has not been clearly established. [7] Other additional ostectomies in combination, that is, Le Fort I and SSRO two-jaw surgery, have been proposed to reduce a large amount of mandibular setback when correcting an excessive anteroposterior discrepancy. A mandibular setback of 15 mm might be the maximum in patients with narrow rami.…”
Section: Apos Trends In Orthodonticsmentioning
confidence: 99%
“…[22][23][24] However, patients with prognathic mandible tend to have a larger upper pharyngeal airway, 25,26 and mandibular setback surgery may not degrade the upper airway patency, 24,27,28 resulting in a very low incidence of obstructive sleep apnea (OSA) after mandibular setback surgery. 28 In the present case, pretreatment oropharyngeal volume and minimal crosssectional area were larger than average for non-OSA subjects, 29,30 and the values decreased at 5-day postsurgery (Fig 11). Irani et al 22 showed that this diminished airway could be improved during postsurgical orthodontic treatment even without significant relapse of mandibular setback surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Orthognathic surgery has been the long mainstay of treatment for correcting skeletal deformities. [1][2][3][4][5][6] Despite its versatility and popularity, some studies note a possible association between orthognathic surgery and posterior airway changes, and consequently exhibiting obstructive sleep apnea (OSA). 2,[7][8][9][10][11][12][13] OSA is defined as a long-term condition, characterized by recurrent episodes of upper airway collapse during sleep.…”
mentioning
confidence: 99%
“…2,[7][8][9][10][11][12][13] OSA is defined as a long-term condition, characterized by recurrent episodes of upper airway collapse during sleep. 6,[14][15][16][17] The prevalence rate of this disorder varies from 3-7% in different populations. [14][15][16][17][18][19] Constant snoring, witnessed apnea, extensive daytime sleepiness, fatigue, and hypoxia are the most common presenting symptoms for patients suffering from OSA.…”
mentioning
confidence: 99%